Improved assay for surface hydrophobic avidity of Candida albicans cells. - Hazen, K C (1990)
A simple method that distinguishes among hydrophobic avidity levels of highly hydrophobic isolates of the pathogenic fungus Candida albicans is described. This method involves mixing polystyrene microspheres at different concentrations with a constant concentration of yeast cells and plotting the data in accordance with the Langmuir isotherm equation. A 10-fold difference between the C. albicans isolates with the lowest and highest avidity (KH) values was found. This method may also demonstrate that surface hydrophobic sites with different avidities are present within a yeast cell population.